Polyelectrolyte conformational transition in aqueous solvent mixture influenced by hydrophobic interactions and hydrogen bonding effects: PAA–water–ethanol - Sappidi, Praveenkumar; Natarajan, Upendra (Journal of molecular graphics & modelling, 2016)
The explicit-solvent atomistic molecular dynamics (MD) simulations of atactic-poly(acrylic acid) (PAA) chain in dilute water–ethanol solution were performed for 0%, 80% and 100% ionization of PAA chain as a function of co-solvent (ethanol) fraction in the range 0–90vol% ethanol (0<ϕeth<0.9). With increase in ϕeth, chain swelling (increase of Rg) is observed for un-ionized PAA (f=0), and chain collapse is observed for partially and fully ionized cases (i.e., f=0.8 and 1). [Display omitted] •Simulations show that un-ionized chain (i.e., f=0) swells and ionized chain (f=0.8 & 1) shrinks with increase in ϕeth, in accordance with experimental observations in literature.•The inter-molecular H-bonds between PAA-solvent increase for un-ionized chain and decrease for ionized chain, as a function ϕeth.•The phase transition point ϕeth=0.4 is comparable to experimental results.•Ionized PAA collapse due to: (i) PAA-solvent (water+ethanol) H-bonds decrease. (ii) PAA-solvent coordination decrease. (iii) Na+ strongly coordinates with COO− group on PAA. Molecular dynamics simulations of poly(acrylic acid) PAA chain in water–ethanol mixture were performed for un-ionized and ionized cases at different degree-of-ionization 0%, 80% and 100% of PAA chain by Na+ counter-ions and co-solvent (ethanol) concentration in the range 0–90vol% ethanol. Aspects of structure and dynamics were investigated via atom pair correlation functions, number and relaxation of hydrogen bonds, nearest-neighbor coordination numbers, and dihedral angle distribution function for back-bone and side-groups of the chain. With increase in ethanol concentration, chain swelling is observed for un-ionized chain (f=0) and on the contrary chain shrinkage is observed for partially and fully ionized cases (i.e., f=0.8 and 1). For un-ionized PAA, with increase in ethanol fraction ϕeth the number of PAA–ethanol hydrogen bonds increases while PAA–water decreases. Increase in ϕeth leads to PAA chain expansion for un-ionized case and chain shrinkage for ionized case, in agreement with experimental observations on this system. For ionized-PAA case, chain shrinkage is found to be influenced by intermolecular hydrogen bonding with water as well as ethanol. The localization of ethanol molecules near the un-ionized PAA backbone at higher levels of ethanol is facilitated by a displacement of water molecules indicating presence of specific ethanol hydration shell, as confirmed by results of the RDF curves and coordination number calculations. This behavior, controlled by hydrogen bonding provides a significant contribution to such a conformational transition behavior of the polyelectrolyte chain. The interactions between counter-ions and charges on the PAA chain also influence chain collapse. The underlying origins of polyelectrolyte chain collapse in water–alcohol mixtures are brought out for the first time via explicit MD simulations by this study.